PERANCANGAN DAN IMPLEMENTASI PRIVATE CLOUD STORAGE DENGAN SEAFILE PADA DEBIAN 9 - santoso, santoso (LPPM Universitasdiwangsa Jambi, 2019)
Storage devices (storage devices) continue to evolve to adjust the needs that are increasingly increasing and more effective. From the start using magnetic tape, floppydisk, magnetic disk, up to hard disk and flashdisk. Storage media has many weaknesses and problems such as viruses, loss of storage devices and often forget to bring. Now there are online data storage providers or cloud storage, but the data that we store is on a server that is owned and managed by the service provider vendor. For data that is privacy or confidential certainly does not guarantee the data is safe. Therefore this research aims to build a personal storage service system (private cloud storage). This private cloud storage service system was designed using a Seafile application and the Debian 9. Linux operating system. This is expected to guarantee security and confidentiality, because the cloud server is built by itself and is used among internal users. The research method in this study uses the SDLC (Systems Development Life Cycle) method consisting of five phases: planning, analysis, design, implementation and maintenance.